The moderating effects of visit Malaysia year towards international tourism demand / Alvin Gatu - Alvin Gatu (2013)
Tourism industry has been an important contributor to the Malaysia’s economy. Malaysia is one of the popular destinations in Asia. The purpose of this study is to estimate tourism demand in Malaysia based on the key economic factor such as inflation rate, exchange rate and gross domestic product by using a modified Gravity Model. Promotional activity known as Visit Malaysia Year is included in this study as a moderating effect. The movement, pattern and changes of the international tourist arrivals are also examined. A cross-sectional pool time-series data the international tourist arrivals was applied by using the modified Gravity Model. The data were constructed from the yearly time series of the number of arriving in Malaysia and the time-series data are covered from year 1990 to 2010. The results show that tourism demand is highly correlated with Gross Domestic Product of the countries which showing the impact on the standard of living. However, tourism demand negatively correlated with Exchange Rate as tourist from higher purchasing power prefers to visit Malaysia. Inflation Rate reduces the number of tourist to travel. On the other hand, Visit Malaysia Year moderates the relationship between inflation ratio, exchange rate, gross domestic product and tourist arrival.